Sex Disparity in Satisfaction and Loyalty Towards Urban Rail Transit: A Survey of Light Rail Transit (LRT) Passengers in Kuala Lumpur, Malaysia - Ibrahim, Ahmad Nazrul Hakimi; Borhan, Muhamad Nazri (International Journal of Integrated Engineering, 2021)
The aim of this study is to explore the effect of sex disparity on passenger satisfaction and loyalty to the light rail transit (LRT) services in Kuala Lumpur, Malaysia. A total of 417 responses from a self-administrated questionnaire were analyzed using non-parametric tests, namely Mann-Whitney U test and Spearman’s correlation test. Based on the Mann-Whitney U test, results showed a significant difference between male and female LRT passengers in terms of their satisfaction and loyalty. In addition, the Spearman’s correlation test proved a significant and positive relationship between passengers’ sex, satisfaction and loyalty. Finally, future suggestions were made based on the findings reported in this study.